Taxation in Democratic State: Quo Vadis Indonesia? - Maria R.U.D. Tambunan (Politeknik Negeri Bali, 2020)
Public participation, interaction among state actors and interest groups in the process of tax policy formulation process is a fundamental mechanism undertaken in democratic state in realizing the agreeable policy. Indonesian taxpayers and citizen as members of democratic state need to quest to what extend state actors have participated on the process of agenda setting until the tax policy has been published to the public. This research is intended to scrutinize the dynamic of state actors' behavior and interest group role on tax policy process in Indonesia and how the measures should be taken to encourage their participation including on improving tax compliance. By using qualitative paradigm, this research is done through documentation and literature study, and technical data analysis in the form of qualitative data analysis with inductive method. The result shows that the state actors had not have sufficient knowledge on taxation issue. Therefore, the discussion on taxation solely relate to how to optimize the state revenue and how the collected revenue could be spent. It needs to optimize public participation on tax policy formulation process that will able to boost tax compliance among the society.